Ideas previas y cambio conceptual en astronomía. Un estudio con maestros de primaria sobre el día y la noche, las estaciones y las fases de la Luna - Camino, Néstor (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this paper we present an experience developed with primary teachers which led to the design of a course, from a constructivistic point of view, on those concepts related to Astronomy included in primary curricula (day and night, seasons, moon phases). With the comparison of pre/post diagnoses (written questions and clinical interviews), we discuss the effectiveness of this conceptual change strategy and make some conclusions, particularly on teacher training.